Transgender identities : towards a social analysis of gender diversity - Hines, Sally; Sanger, Tam (Routledge research in gender and society, 2010)
This volume offers vivid accounts of the diversity of living transgender in today's world, representing the cutting-edge scholarship in transgender studies. This book will be of interest to scholars and students in sociology and gender and sexuality studies.